Banker or Benefactor? Chinese Foreign Aid and Economic Inequality in Africa, 2000-2018 - Miller, Rachel L. (Tufts Archival Research Center, 2022)
This paper utilizes a comprehensive dataset of Chinese official financing activities in Africa, between the years 2000 to 2018, to study the effects of Foreign Direct Investment (FDI) inflows. Using cross-country variation in exogenous geographic characteristics, the paper estimates the causal effect of Chinese aid on economic inequality in Africa. The results demonstrate that Chinese foreign aid significantly increases short-term economic inequality in recipient African countries.; Thesis (B.S.)--Tufts University, 2022.; Submitted to the Dept. of Economics.